Macroeconomic factors effect on housing price index in China - Li, Zheyu (2015)
There are lots of empirical studies and theory concluded that house price able to reflect economic fundamentals in the long-term. However, based on empirical analysis in the context, it has been seen that house price has deviated upward from the economic fundamentals since the Chinese government started macro-control of the real estate market. It is considered that the mechanism between the economic fundamentals and house price were distorted by China’s real estate policy, particularly its’ land policy. However, the policy itself is a significant factor in explaining the changes of China’s housing price. The study was conducted by estimating different data model on house price using statistical models and the variables which are controlled by real estate policy. The result shows that land supply and other variables has negative effects on house price, and also that financial mortgages for real estate have positive effects on house price; and the area of vacant houses as well as the area of housing sold, which reflects the demand and supply of the housing market, showing a negative effects on house price. The study also finds some differences in house price influence factor between cities in China. In conclusion, the study proposes policy suggestions according to the empirical results obtained.